Algerian Constitutional Judiciary: The First Steps in the Experience of Reviewing the Exception of Unconstitutionality - Belmahdi, Brahim (Journal of Legal Studies and Researches, 2026)
This study addresses the characteristics of the decisions of the Algerian constitutional judiciary related to the exception of unconstitutionality, to protect rights and freedoms, after the litigants raised their pleas before the judicial authorities regarding some legislative provisions, including those related to equality and litigation at two levels, and Then it is referred by the Supreme Court and the Council of State for consideration by the Constitutional Council in its short experience and later by the Constitutional Court.